2013
DOI: 10.4236/ojped.2013.34054
|View full text |Cite
|
Sign up to set email alerts
|

Delivery and evaluation of a pilot obesity prevention project for urban Appalachian children

Abstract: Prevention of childhood obesity is a national concern and there is a need for interventions that can be implemented in community programs and are brief in nature. This pilot project was developed to evaluate the impact of the Children's Healthy Eating and Exercise Program, which was adapted from the Traffic Light Diet. Participants were urban Appalachian children and adolescents who were enrolled in one of two community-based summer programs. Quantitative and qualitative methods were used to examine children's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Findings indicated that children in the intervention group were learning about red and green light foods. These findings are consistent with other studies indicating the acceptability and feasibility of the adapted Traffic Light Diet for children [21,22]. Children in the intervention and comparison groups were eating more vegetables at the post-intervention assessment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings indicated that children in the intervention group were learning about red and green light foods. These findings are consistent with other studies indicating the acceptability and feasibility of the adapted Traffic Light Diet for children [21,22]. Children in the intervention and comparison groups were eating more vegetables at the post-intervention assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Results also indicated that children displayed knowledge of the green and red light food categories, but were less knowledgeable about yellow light foods. There was no significant change in levels of exercise at the end of the program [21]. Thus, the current study added a more intensive physical activity program, having more equipment available for children to use and more time to engage in physical activities at each session.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Questions assessing healthy eating were used pre- and post-intervention. 7 The questions assessed consumption of fruits, vegetables, and sweets—“yesterday.” Line-drawings of many types of fruits (eg, strawberries, grapes, apples, oranges), vegetables (eg, broccoli, carrots, green beans), and sweets (eg, cake, donuts, cookies, pie, candy bars) accompanied the questions. Children rated their answers on the following scale: (1) “No, I didn’t eat any.…”
Section: Methodsmentioning
confidence: 99%
“… 5 The Children’s Healthy Eating and Exercise (CHEE) Program is an after-school program with a successful history of improving children’s consumption of healthy foods, with children eating more fruits, exercising more, and children and parents learning about nutrition. 2 , 6 - 9 More information is needed about how children change their and their family’s eating behaviors. The current study focused on delivering and assessing the impact of healthy eating lessons using photovoice to allow children to capture change in eating behaviors.…”
Section: Introductionmentioning
confidence: 99%